Zasada domniemania niewinności — próba spojrzenia materialnoprawnego - Lipiński, Konrad (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article concerns the relationship between presumption of innocence and elements of the dogmatic structure of crime, particularly guilt. It appears that the presumption of innocence has nothing to do with guilt conceived as personalized blame, and it is doubtful to what extent — if at all — it extends to other elements of criminal act. The presumption of innocence seems to be domain of facts, not necessarily law.
Keywords: presumption of innocence; guilt; dogmatic structure of crime